Frontispiece: An Aromatic Hydroxyamide Attenuates Multiresistant Staphylococcus aureus Toxin Expression. Issue 5 (20th January 2016) - Vomacka, Jan; Korotkov, Vadim S.; Bauer, Bianca; Weinandy, Franziska; Kunzmann, Martin H.; Krysiak, Joanna; Baron, Oliver; Böttcher, Thomas; Lorenz‐Baath, Katrin; Sieber, Stephan A.
Abstract : Anti‐Virulence Strategy The agreement depicted in the figure is between humans, who, instead of killing bacterial cells, just reduce their arsenal of virulence factors, and Staphylococcus aureus which, as a reward, do not respond with resistance development. In their Full Paper onpage 1622 ff., S. A. Sieber et al. report that the molecule represented in the middle and on the contract is one of the most powerful among a set of hydroxyamide derivatives to exhibit this remarkable bioactivity.